Perlindungan Hukum Terhadap Pekerja PKWT Dalam Pemberian Uang Kompensasi - Indra Agus Priyanto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
In this era of globalization where the economy is advancing rapidly so that many competitors have sprung up in the economic sector, to create a conducive climate both in terms of the economy, licensing and employment, the government has created a regulation, namely the Omnibus Law which aims to create a quality business and investment climate for business people, including MSMEs and foreign investors. In realizing this, the Government issued Law No. 11 of 2020 which has been revoked by Perpu No.2 of 2022 concerning Job Creation and its implementing regulations in the field of Manpower issued PP No. 35 of 2021 with the aim of providing legal protection and welfare for workers, but this research needs to be reviewed because there are deletions, updates, and insertions of articles regarding labor law. Among the updates to these rules, what is discussed in this study is the analysis of the rules for Fixed-Term Employment Agreements (PKWT) in the Job Creation Law. There is a change in the PKWT regulation, namely workers/laborers whose contract period has ended, are entitled to receive compensation money. This is a new thing, so the purpose of this study is to analyze normative juridical rules regarding the provision of compensation or severance pay from the start of the distribution of the amount and sanctions for companies if they violate it.